Penerapan Pengendalian Persediaan Bahan Baku Roti Dengan Metode Economic Order Quantity (EOQ) Pada Studi Kasus Sektor Produksi Roti: Implementation of Bread Raw Material Inventory Control Using the Economic Order Quantity (EOQ) Method in a Case Study of the Bread Production Sector - Sinaga, Michael; Syarif, Abdul Azis (INVANTRI (Inovasi Dan Pengelolaan Industri), 2025)
A company's continuous production process is influenced by factors such as technology, capital, inventory of goods, raw material inventory, and labor. Inventory factors have an important role in a production process, where the company's inventory of raw materials aims to ensure the continuity of the company's production process. One of them is factory X's bread production sector because the factory owner has not used any inventory control system in his factory. This is shown by the high inventory costs using the MRP method and resulting savings compared to the company's manual method. Optimizing raw material supplies for bread factories can also be done using the Economic Order Quantity (EOQ) method. This is proven by the results of Lot Sizing calculations with raw material inventory costs of IDR 20,266,298, while costs for ordering goods are IDR 19,776,000 and for storing goods IDR 11,761,500 per year.